The Impact of Organizational Commitment on Improving the Quality of Services Provided in the Presence of a Learning Organization - Al-Aqrabawi, Rowaida; Alkhazali, Zeyad; Rumman, Amani Abu; Alshawabkeh, Rawan; Al-Abbadi, Lina Hamdan (Journal of Ecohumanism, 2025)
The research aimed to investigate the impact of organizational commitment on improving the quality of services provided in the presence of the learning organization. The research variables were organizational commitment as an independent variable with its three dimensions (emotional commitment, mandatory commitment, and ethical commitment), the quality of services provided as a dependent variable, and the learning organization as an intervening variable. To achieve the research objectives, the descriptive analytical approach was used. A questionnaire was designed and used as a tool for collecting data. The research sample amounted to (374) individuals. The questionnaire was distributed to the research sample. (362) forms were retrieved. The number of forms valid for statistical analysis amounted to (350) forms. The research concluded with several results, the most important of which is the existence of a statistically significant moral effect of organizational commitment on the quality of services provided. The research also found a statistically significant moral effect of the emotional commitment dimension, the mandatory commitment dimension, and the ethical commitment dimension on the quality of services provided. The research also found a statistically significant moral effect of the learning organization on the relationship between organizational commitment and the quality of services provided.